2017
DOI: 10.2214/ajr.16.17117
|View full text |Cite
|
Sign up to set email alerts
|

DWI for Assessment of Rectal Cancer Nodes After Chemoradiotherapy: Is the Absence of Nodes at DWI Proof of a Negative Nodal Status?

Abstract: Although the absence of nodes at DWI is not a frequent finding, it appears to be a reliable predictor of yN0 status after CRT in patients with rectal cancer. DWI may thus be a helpful adjunct in assessing response after CRT and may help select patients for organ-saving treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 37 publications
(59 reference statements)
0
26
0
5
Order By: Relevance
“…After CRT, evaluating nodal size in the short axis is more reliable than evaluating borders and shape to assess for residual malignancy (33). The absence of lymph nodes at DWI, the decrease in size in at least 70% of lymph nodes, and a nodal size less than 2.5 mm in the short axis have been shown to be reliable predictors of negative node status after surgery (Fig 16) (71).…”
Section: Assessing Other Posttreatment Featuresmentioning
confidence: 99%
“…After CRT, evaluating nodal size in the short axis is more reliable than evaluating borders and shape to assess for residual malignancy (33). The absence of lymph nodes at DWI, the decrease in size in at least 70% of lymph nodes, and a nodal size less than 2.5 mm in the short axis have been shown to be reliable predictors of negative node status after surgery (Fig 16) (71).…”
Section: Assessing Other Posttreatment Featuresmentioning
confidence: 99%
“…Accordingly, a recent consensus statement recommended using nodal size for follow-up assessment after neoadjuvant therapy (with nodes whose short axis diameter is < 5 mm considered benign), given the absence of other reliable criteria[ 16 ]. However, several studies have reported the presence of small groups of residual cancerous cells in a significant number of small nodes (up to 3 mm), a finding that limits the sensitivity of this criterion[ 67 , 69 , 70 ]. Some authors have suggested that these foci could show a late response to treatment, but this hypothesis is unconfirmed and controversial[ 10 , 71 , 72 ].…”
Section: Diagnosis and Reassessmentmentioning
confidence: 99%
“…Both the accuracy for assessing response and interreader agreement improved significantly compared to the more well-known 5-point mrTRG score which uses T 2 W-MRI only. 46 A single report by Park and colleagues evaluated the use of DWI in addition to T 2 W-MRI to predict tumour clearance of the MRF after neoadjuvant CRT. 38 The authors reported a significantly improved performance after the addition of DWI (AUC 0.92-0.96) compared to use of only T 2 W MRI (AUC 0.77-0.85).…”
Section: Tumour Restagingmentioning
confidence: 99%